Assessment of Roadside Soil Pollution by Heavy Metal Ions and Correlation to Traffic Activities in Madina City, Saudi Arabia: Part I - Assirey, E.; El-Shahawi, M.S. (Asian Journal of Chemistry, 2015)
Traffic activities are considered as one major sources of heavy metal pollution in roadside soil. Therefore, this study was carried out to investigate the impact of traffic on the characteristics of heavy metals in roadside soil of Madina city, Saudi Arabia. Soil samples from the surface and 20 cm under surface in 12 different sites were collected and analyzed for As, Co, Pb, V and Zn. The traffic density was monitored in roads near the sampling sites and correlated with heavy metal concentration to investigate the impact of traffic density on heavy metal ions concentration. The results revealed great dependence of Pb and Zn on traffic density with correlation coefficients of 0.991 and 0.987, respectively. The other metals, As, Co and V showed no dependence on traffic density and no dependence between the surface and under surface concentration. The values of pollution indices such as contamination factor, degree of contamination and geo-accumulation index (Igeo) indicated various levels of contamination in the roadside soil in some study sites. The degree of contamination values in the more polluted site were 32.192, 28.872 and 23.902 in the airport road (1), Taibah University street (2) and Orwah valley street (3). These results ensure that traffic emissions, automobiles and other anthropogenic activities are major sources of the metal contamination.